RESPON PERKECAMBAHAN KELAPA SAWIT (Elaeis guineensis Jacq) TERHADAP KONSENTRASI DAN LAMA PERENDAMAN GIBERELIN (GA3) YANG BERBEDA - Refita Rizki; Syaiful Anwar; Florentina Kusmiyati (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2022)
The study aimed to examine the growth response of oil palm (Elaeis guineensis Jacq) sprouts to different concentrations and immersion times of gibberellins (GA3). The research was conducted from September – January 2022 in Ds. Sikabau, Kec. Kotobalingka, Kab. Pasaman Barat. Research data analysis was conducted at the Laboratory of Physiology and Plant Breeding, Faculty of Animal and Agriculture Science, Diponegoro University, Semarang, Central Java. The experimental design used in this study was a Factorial Completely Randomized Design (CRD) 4 x 3 with 3 replications so that there were 36 experimental units. The first factor was immersion at various concentrations of gibberellin (GA3) which consisted of four treatment levels: A0: immersion with control (aqua dest), A1: 100 ppm, A2: 200 ppm, and A3: 300 ppm. The second factor was the immersion time which consisted of three treatment levels: W1: 3 days, W2: 6 days, and W3: 9 days. Parameters observed included germination, maximum growth potential, growth simultaneously, plant height, and canopy wet weight. The results showed that the duration of the seed soaking treatment for oil palm did not have a significant effect on all research parameters. The treatment of oil palm seed soaking doses of 200 ppm and 300 ppm significantly affected the doses of 100 ppm and 0 ppm on the parameters of germination, vigor index, growing simultaneously, number of leaves, plant height, leaf area, canopy wet weight and root length of oil palm plants. The results showed that the administration of 200 ppm GA3 gave the best results for oil palm seed growth and the immersion time did not significantly affect all research parameters. The conclusions of this study indicate that the 100 ppm GA3 immersion treatment and 9 days of immersion according to the hypothesis did not give the best growth results.